2013
DOI: 10.1590/s0006-87052013000200002
|View full text |Cite
|
Sign up to set email alerts
|

Estimativas de parâmetros genéticos e ganho de seleção para produção de frutos em progênies de polinização aberta de pupunheira no estado do Pará, Brasil

Abstract: O estudo objetivou estimar parâmetros e valores genéticos para os caracteres número de cachos (NC), peso médio do cacho (PMC) e peso total do cacho (PTC) aos seis anos, pelo método de modelos mistos (REML/BLUP). O teste de progênies foi estabelecido sob o delineamento de blocos ao acaso com 50 tratamentos (progênies), 10 blocos e uma planta por parcela, no espaçamento de 5 x 5 m, além de uma bordadura externa ao experimento. As estimativas de herdabilidade individual e médias no sentido restrito para PTC (0,21… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 7 publications
1
14
0
2
Order By: Relevance
“…Genetic variability can also be confirmed and quantified by the coefficient of genetic variation (Cvg), which expresses the magnitude of genetic variation in relation to the trait average (Farias Neto et al, 2013). The estimated Cvg values in the present study reinforce the genetic variability present among accessions (Table 5), as shown by cluster analysis (Table 2) and by the heritability values presented above.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Genetic variability can also be confirmed and quantified by the coefficient of genetic variation (Cvg), which expresses the magnitude of genetic variation in relation to the trait average (Farias Neto et al, 2013). The estimated Cvg values in the present study reinforce the genetic variability present among accessions (Table 5), as shown by cluster analysis (Table 2) and by the heritability values presented above.…”
Section: Discussionsupporting
confidence: 80%
“…Quantifying genetic diversity and determining its magnitude by efficient methods of estimation help to successfully select the best individuals to establish the next generation, maximizing genetic gains and efficiency in the development of new cultivars (Farias Neto et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The genetic improvement depends on the correct choice of the best individuals that will be used as parents, and the genetic parameters estimation is the indispensable basis for the success of the breeding program, according to Farias Neto et al (2013).…”
mentioning
confidence: 99%
“…Thus, the study of genetic parameters is fundamental in the design of the most efficient strategies for gains in production and yield. Studies have estimated genetic parameters of several species of palma of commercial interest (FARIAS NETO et al, 2004;OLIVEIRA & MOURA, 2010;MANFIO et al, 2011), including peach palm (FARIAS NETO & RESENDE, 2001;FARIAS NETO et al, 2013;KHALIL FILHO & RESENDE, 2011, PADILHA et al, 2003. In the state of Acre, experiments with peach palm progenies are in progress (BERGO et al, 2013, NEGREIROS et al, 2013, which has provided the basis for selection of superior plants with consequent improvement of species.…”
Section: Introductionmentioning
confidence: 99%